Continuous Separation of Cesium Based on NiHCF/PTCF Electrode by Electrochemically Switched Ion Exchange - 孙斌 郝晓刚 王忠德 张忠林 刘世斌 官国清 (Chinese journal of chemical engineering, 2012)
Nickel hexacyanoferrate （NiHCF） film was synthesized on porous three-dimensional carbon felt （PTCF） substrate by repetitious batch chemical depositions, and the NiHCF/PTCF electrode was used as electrochemically switched ion exchange （ESIX） electrode in a packed bed for continuous separation for cesium ions. The morphologies of the prepared electrodes were characterized by scanning electron microscopy and the effects of solution concentration on the ion-exchange capacity of the electrodes were investigated by cyclic voltammetry technique. Cycling stability and long-term storage stability of NiHCF/PTCF electrodes were also studied. The NiHCF/PTCF electrodes with excellent ion-exchange ability were used to assemble a diaphragm-isolated ESIX reactor for cesium separation. Continuous separation of cesium and regeneration of NiHCF/PTCF electrode based on the diaphragm-isolated reactor were performed in a laboratory-scale two-electrode system.